2021
DOI: 10.1016/j.telpol.2021.102125
|View full text |Cite
|
Sign up to set email alerts
|

ICT dynamics for gender inclusive intermediary education: Minimum poverty and inequality thresholds in developing countries

Abstract: This study examines linkages between information and communication technology (ICT) dynamics, inequality and poverty in order to establish critical masses of poverty and inequality that should not be exceeded in order for ICT dynamics to promote gender inclusive education in 57 developing countries for the period 2012-2016. Poverty is measured with the poverty headcount ratio at national poverty lines (% of the population) while inequality is proxied by the Gini coefficient, the Atkinson index and the Palma ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…Thus, if there is an increase in ICT by 1 percent, it will reduce poverty by -0.0043 percent. In the long run, ICT accepts H 2 and rejects H 0 .This result is in line with research Ahmed & Al-Roubaie (2013); Setyaningsih (2017); Nisa & Budiarti (2020); Mushtaq & Bruneau (2019); Mora-Rivera & García-Mora (2021); Asongu et al (2021); Christiani & Nainupu (2021) and Yin et al (2021) which found that ICT had a statistically significant negative effect on poverty. In 2007, it was reported that there were 20 million internet users in Indonesia.…”
Section: Panel Test Using Error Correction Modelsupporting
confidence: 87%
See 1 more Smart Citation
“…Thus, if there is an increase in ICT by 1 percent, it will reduce poverty by -0.0043 percent. In the long run, ICT accepts H 2 and rejects H 0 .This result is in line with research Ahmed & Al-Roubaie (2013); Setyaningsih (2017); Nisa & Budiarti (2020); Mushtaq & Bruneau (2019); Mora-Rivera & García-Mora (2021); Asongu et al (2021); Christiani & Nainupu (2021) and Yin et al (2021) which found that ICT had a statistically significant negative effect on poverty. In 2007, it was reported that there were 20 million internet users in Indonesia.…”
Section: Panel Test Using Error Correction Modelsupporting
confidence: 87%
“…Mushtaq & Bruneau (2019) conducted a case study by assessing the role of Information and Communication Technology (ICT) in poverty reduction, using a collection of panel data from 62 (sixty-two) countries between 2001-2012. Asongu et al (2021) examined the relationship between ICT dynamics in 57 developing countries from 2012-2016. Ahmed & Al-Roubaie (2013) examines the role of ICT in reducing poverty in Arab countries in achieving sustainable development.…”
Section: Introductionmentioning
confidence: 99%
“…This ever-growing evolution of ICTs has led policy makers and researchers alike to take a greater interest in the effects of ICTs on different aspects of socio-economic and political life. Thus, it has been demonstrated in the literature, although not exhaustive, that ICTs have positive effects, on employment (Mbongo and de Berquin 2019 ; Kılıçaslan and Töngür, 2019 ), trade (Abeliansky et al 2021 ); industrialisation (Njangang and Nounamo 2020 ); environment quality (Avom et al 2020 ; Asongu et al 2018 ; Higón et al 2017 ); corruption reduction (Sassi and Ali 2017 ; Kanyam et al 2017 ); democracy (Ali 2020 ); health outcomes (Dutta et al 2019 ); education (Asongu et al 2021 ); poverty reduction (Ofori et al 2021 ); income inequality reduction (Asongu and Odhiambo 2019 ), and most importantly economic growth (Sawng et al 2021 ; Appiah-Otoo and Song 2021 ; Hong 2017 ; Ofori and Asongu 2021 ; Ofori et al 2022 ). Despite this dynamic and extensive literature, very few studies have looked at the effect of ICT on economic complexity.…”
Section: Introductionmentioning
confidence: 99%
“…Data is a new factor of production in the context of the digital economy, which has brought about profound changes in production, consumption, exchange and distribution. The digital economy's scale effect, low transaction cost and wide penetration are the most essential properties that influence the "inclusive" and "green" components ( Asongu et al, 2021;Shahbaz, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%